2013
DOI: 10.1002/2013jc009367
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of the seasonal variation in the South China Sea throughflow transport

Abstract: [1] The Luzon Strait transport (LST) of water mass from the Pacific Ocean to the South China Sea (SCS) varies significantly with seasons. The mechanisms for this large variability are still not well understood. The steady-state island rule, which is derived from a steadystate model, is not applicable to seasonal time scale variations in a large basin like the Pacific Ocean. In this paper, we will use a theoretical model that is based on the circulation integral around the Philippines. The model relates the LST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Results show that this simple model can adequately capture the mean and seasonal cycle of NBL (Figure a). Specifically, the MMM position of NBL and its seasonal migration amplitude are 15.0°N and 0.92°, in good agreement with recent observations and modeling studies [e.g., Yaremchuk and Qu , ; Chen and Wu , ; Yang et al , ; Zhai et al , ].…”
Section: Role Of Wind Forcing and Ocean Stratificationsupporting
confidence: 89%
“…Results show that this simple model can adequately capture the mean and seasonal cycle of NBL (Figure a). Specifically, the MMM position of NBL and its seasonal migration amplitude are 15.0°N and 0.92°, in good agreement with recent observations and modeling studies [e.g., Yaremchuk and Qu , ; Chen and Wu , ; Yang et al , ; Zhai et al , ].…”
Section: Role Of Wind Forcing and Ocean Stratificationsupporting
confidence: 89%
“…Yang et al . [] find that Kuroshio weakens and Mindanao strengthens as the bifurcation shifts northward and that the westward flow into the South China Sea via Luzon Strait increases. On the interannual time scale, results both from high‐resolution general circulation models [ Kim et al ., ] and from satellite altimetry analysis [ Wang and Hu , ; Qiu and Chen , ] have consistently indicated that the bifurcation latitude of the NEC moves northward during El Niño years, resulting in a minimum transport of the Kuroshio east of Luzon [e.g., Kim et al ., ; Qu and Lukas , ].…”
Section: Discussionmentioning
confidence: 99%
“…Its transport across the observed section attained the peak in January and trough in June, with a peak‐to‐trough amplitude of 2.8 Sv. This seasonal variability is consistent with the annual migration of the North Equatorial Current (NEC) bifurcation, as already noted by previous studies [e.g., Qu and Lukas , ; Qu et al ., ; Yaremchuk and Qu , ; Qiu and Chen , ; Yang et al ., ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Based on historical hydrographic data, previous literatures found that the LST has a distinct annual cycle, stronger in boreal winter and weaker in summer seasons [ Wyrtki , ; Shaw , ; Qu , ]. This kind of seasonal variability could be attributed to the seasonally reversing East Asia monsoon [ Farris and Wimbush , ; Metzger and Hurlburt , ; Hsin et al ., ; Wu and Hsin , ], as well as the influence of the boundary current east of the Philippines [ Yaremchuk and Qu , ; Qu et al ., ; Yang et al ., ]. Analysis of altimeter observations and model products also suggested that the LSZF and LST have significant interannual and decadal variabilities.…”
Section: Introductionmentioning
confidence: 99%